Caracterización de los residuos sólidos domiciliarios generados en el asentamiento humano Monte Sion, San Juan Bautista, 2020 - Tuesta Torres, Roberto Carlos (2022)
This thesis work was developed in the Monte Sion Human Settlement located at km 3 on the left side of the Iquitos - Nauta interprovincial highway, the evaluation was carried out during the months of April to September 2020; and its general objective was to carry out the characterization of household solid waste, in addition, the generation per capita, the density of these wastes was determined; and the opinion of the inhabitants was recorded through the application of a survey related to the disposal and segregation of solid waste in the Monte Sion Human Settlement, whose purpose was to know the types and amount of waste that is generated there; improving its segregation and disposal, in order to reduce the level of contamination. From the analysis and processing of the information collected on the weight of the waste, and from the survey applied to the inhabitants of the Monte Sion Human Settlement, a value of 9,600,400 kg was obtained, with organic matter being the largest waste generated with a value 6,534 kg, followed by plastic with 1,478,400 kg, paper with 672,700 kg, cardboard with 530,100 kg, metal with 206,200 kg, and glass with 179 kg.